Review of glass fiber reinforced of epoxy based composite materials - Najafi, Hamideh; Mohammad Khani, Behzad (Journal of Composites and Compounds, 2025)
Recently, glass fiber-reinforced epoxy composite materials have shown great promise for a variety of applications. This review offers an in-depth overview of these composites, focusing on their core components, manufacturing processes, and performance characteristics such as mechanical strength and thermal stability. It discusses various types of glass fibers and epoxy resin formulations, alongside advanced fabrication methods like vacuum infusion, and Resin Transfer Molding which significantly influence their structural robustness and application flexibility. The review examines critical mechanical properties including tensile, flexural, impact, and fatigue behaviors as well as thermal and chemical durability essential for challenging operational environments. Additionally, the study highlights the mechanical and thermal responses of different glass fiber reinforced polymer composites under load, emphasizing their significance in modern industry sectors. Insights into their multiple applications—from automotive and construction to marine and recreational products are provided, illustrating their growing importance in engineering advancements. The conclusion underscores ongoing challenges and future opportunities in optimizing epoxy-glass fiber composites to meet emerging technological demands.